(untitled) (Research, Society and Development, 2021)
The medical field has wide career preferences as the medical world develops, making it attractive for students to study medicine. The breadth of career preferences in the medical field exposes students to various career options according to their wishes and abilities. Insight into medical career preferences will help students determine the right medical career. This study aims to determine the determinants of career preferences of medical preclinical students in general in Indonesia. This study used a method descriptive cross-sectional. The data is the result of the questionnaire in accordance with the inclusion criteria of the sample. The number of samples obtained was 145 medical preclinical students at the Faculty of Medicine, Udayana University. From the results of the study, it was found that 138 students (95.2%) chose a career as a clinician and 7 students (4.8%) chose a career as a non-clinical doctor. Students who choose clinicians, choose a pediatrician and internal medicine specialist as many as 22 students (16.2%). Pre-clinical blocks that are preferred by students are Behavior 87 students (60%) and Endocrine 24 students (16.6%). Parental background, cost, and time required for further education are not obstacles for respondents to choose their career preferences.